2001
DOI: 10.1074/jbc.m010027200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two GDP-6-deoxy-d-lyxo-4-hexulose Reductases Synthesizing GDP-d-rhamnose in Aneurinibacillus thermoaerophilus L420-91T

Abstract: The glycan repeats of the surface layer glycoprotein of Aneurinibacillus thermoaerophilus L420-91 T contain Drhamnose and 3-acetamido-3,6-dideoxy-D-galactose, both of which are also constituents of lipopolysaccharides of Gram-negative plant and human pathogenic bacteria. The two genes required for biosynthesis of the nucleotide-activated precursor GDP-D-rhamnose, gmd and rmd, were cloned, sequenced, and overexpressed in Escherichia coli. The corresponding enzymes Gmd and Rmd were purified to homogeneity, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 50 publications
4
72
0
Order By: Relevance
“…Interestingly, the natural pathways of GDP-D-rhamnose biosynthesis have been elucidated for a number of bacterial species and are found to involve conversion of GDP-D-mannose in a two-step process, utilizing a homologous GDP-mannose dehydratase and second reductase enzyme (65). A GMD from Aneurinibacillus thermoaerophilusthis was similarly reported to catalyze both dehydratase and reductase reactions to produce a rhamnose product, albeit less efficiently than the natural reductase enzyme (66).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the natural pathways of GDP-D-rhamnose biosynthesis have been elucidated for a number of bacterial species and are found to involve conversion of GDP-D-mannose in a two-step process, utilizing a homologous GDP-mannose dehydratase and second reductase enzyme (65). A GMD from Aneurinibacillus thermoaerophilusthis was similarly reported to catalyze both dehydratase and reductase reactions to produce a rhamnose product, albeit less efficiently than the natural reductase enzyme (66).…”
Section: Resultsmentioning
confidence: 99%
“…This intermediate is then converted by GFS into GDP-L-fucose, which can be converted by GDP-4-keto-6-deoxy-D-mannose reductase (RMD) into GDP-Drhamnose (Maki & Renkonen, 2004). Kneidinger et al (2001) found a bifunctional enzyme with both GMD and RMD activities in Aneurinibacillus thermoaerophilus. This enzyme shows 45 and 55 % identity with pRhico007 and pRhico008-009 products, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…GKDM is eventually converted to GDP-fucose by several downstream enzymatic reactions. In bacteria, however, GKDM can be reduced to form GDP-rhamnose by a GDP-4-keto-6-deoxy mannose reductase (RMD) 87 . GDP-rhamnose is a common component of bacterial cell surface glycans.…”
Section: Strategies To Produce Afucosylated Antibodiesmentioning
confidence: 99%